Association between fear of cancer recurrence and emotional distress in breast cancer: a latent profile and moderation analysis - Jiang, Yingting; Li, Hongman; Xiong, Ying; Zheng, Xiaoting; Liu, Yanjun; Zhou, Jian; Ye, Zengjie (Frontiers in Psychiatry, 2025)
BackgroundBreast cancer patients often experience significant psychological challenges, particularly fear of cancer recurrence (FCR), which is a prevalent and distressing concern following diagnosis. FCR can lead to heightened emotional distress, including anxiety and depression. Resilience, the ability to adapt positively to adversity, may play a crucial role in mitigating these negative emotional outcomes. This study aims to explore the heterogeneity of FCR among breast cancer patients and examine the moderating effect of resilience on the relationship between FCR and emotional distress.Materials and methodsA cohort of 398 breast cancer patients participated in the Be Resilient to Breast Cancer (BRBC) program between May and December 2023. Surveys were administered to assess FCR, resilience, and emotional distress levels. Data were analyzed using two approaches: latent profile analysis (LPA) to identify distinct FCR profiles and moderation analysis to evaluate the role of resilience.ResultsThree distinct FCR profiles were identified: low (27.5%), middle (53%), and high (19.5%). Resilience significantly moderated the association between FCR and anxiety (B = 0.115, SE = 0.046, P = 0.014), but no significant moderating effect was observed for depression.DiscussionThe findings highlight significant heterogeneity in FCR among breast cancer patients, with a substantial proportion experiencing moderate to high levels of FCR. Resilience was found to buffer the impact of FCR on anxiety, suggesting that interventions aimed at enhancing resilience could alleviate anxiety related to FCR in this population. These results underscore the importance of incorporating resilience-focused strategies into psychological therapies for breast cancer patients.